2022
DOI: 10.1590/fst.53822
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic potential analysis and fumigation treatment of three Fusarium spp. strains isolated from Fusarium head blight of wheat

Jin WANG,
Yuxi GU,
Yuchong ZHANG
et al.

Abstract: Fusarium Head Blight (FHB) of wheat and small grain cereals caused by Fusarium graminearum and other Fusarium species is an economically cereal disease worldwide. Fusarium infections results in reduced yields and mycotoxin contamination of the grain, and the research on the toxin production and growth control of Fusarium is the key to prevent and control of mycotoxin contamination in wheat. In this study, the molecular identification of toxigenic potential and gas fumigation control of typical Fusarium strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…It has been reported that 25-50% of the crops harvested in the world each year are contaminated with mycotoxins (Ricciardi et al, 2013). Reactions during food processing have shown that DON and OTA can occur in cereals (Wang et al, 2022). The main factors that increase mold growth and mycotoxin biosynthesis in stored grains are known as high grain moisture (16-30%), high grain temperature (25-32 °C), and high air relative humidity (80-100%) (Shanahan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 25-50% of the crops harvested in the world each year are contaminated with mycotoxins (Ricciardi et al, 2013). Reactions during food processing have shown that DON and OTA can occur in cereals (Wang et al, 2022). The main factors that increase mold growth and mycotoxin biosynthesis in stored grains are known as high grain moisture (16-30%), high grain temperature (25-32 °C), and high air relative humidity (80-100%) (Shanahan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%